2021
DOI: 10.1016/j.jare.2020.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-activated Cl− channel TMEM16A inhibition by cholesterol promotes angiogenesis in endothelial cells

Abstract: Graphical abstract Cholesterol reduces TMEM16A expression via DNMT1-mediated promoter methylation and directly inhibits channel activities. TMEM16A inhibition promotes endothelial angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Inhibiting ANO1 significantly rescued OGD/R-induced downregulation of TJ proteins and upregulation of BBB permeability in vitro ( Liu et al, 2019 ). And the present studies showed that ANO1 affects the functions of brain capillary endothelial cells, which are involved in BBB functions ( Suzuki et al, 2020 ; Liu et al, 2021 ; Ma et al, 2021 ; Suzuki et al, 2021 ).…”
Section: Introductionsupporting
confidence: 55%
“…Inhibiting ANO1 significantly rescued OGD/R-induced downregulation of TJ proteins and upregulation of BBB permeability in vitro ( Liu et al, 2019 ). And the present studies showed that ANO1 affects the functions of brain capillary endothelial cells, which are involved in BBB functions ( Suzuki et al, 2020 ; Liu et al, 2021 ; Ma et al, 2021 ; Suzuki et al, 2021 ).…”
Section: Introductionsupporting
confidence: 55%
“…Firstly, the Student’s t-test, non-parametric test, chi-square test, or one-way analysis was used to check whether there were significant differences on the demographic data among the three groups ( Ma et al., 2021 ). Secondly, the orthogonal partial least-square discriminant analysis (OPLS-DA) was used to identify the differential genera responsible for the discrimination between MDD patients and HC.…”
Section: Methodsmentioning
confidence: 99%
“…In human aortic ECs, TMEM16A is a negative regulator of proliferation, migration and angiogenesis. TMEM16A inhibition by cholesterol contributes to endothelial dysfunction ( Ma et al, 2021 ). In HUVECs, TMEM16A is a positive regulator of reactive oxygen species generation, which induces endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Human umbilical vein endothelial cells (HUVECs) were commonly used for angiogenesis studies ( Nowak-Sliwinska et al, 2018 ). TMEM16A is expressed in several EC types and displays dissimilar even paradoxical functions ( Wu et al, 2014 ; Ma et al, 2017 ; Ayed et al, 2018 ; Liu et al, 2019 ; Suzuki et al, 2020 ; Ma et al, 2021 ). The relationship between TMEM16A and angiogenesis under stress is unknown.…”
Section: Introductionmentioning
confidence: 99%